Effect of transpiration suppressants and nutrients on productivity and moisture-use efficiency of pearlmillet (Pennisetum glaucum) – pigeonpea (Cajanus cajan) intercropping system under rainfed conditions - Ansari, M A; Rana, K S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted at IARI, New Delhi during 2009 and 2010 to study the effect of cropping systems, transpiration suppressants and nutrient management on productivity and moisture-use-efficiency of pearlmillet (Pennisetum glaucum L.) – pigeonpea [Cajanus cajan (L.) Millsp.] intercropping system under rainfed conditions on a sandy loam soil. There was significant superiority in yield attributes as well as yield of pearlmillet and pigeonpea under sole cropping as compared to their intercropping system. Pearlmillet equivalent yield and land equivalent ratio was significantly higher with intercropping system (2:1 ratio). Intercropping system recorded the higher moisture-use-efficiency and economics as compared to either of the sole cropping. Rate of moisture use was more in sole pearlmillet (3.92 mm/day) than sole pigeonpea and intercropping system. The results showed significant improvement in all yield attributes and yield as well as moisture use and economics due to spray of transpiration suppressants over the control under inadequate moisture conditions. The total number of nodule and nitrogenase activity significantly differed in pigeonpea crop under different fertilizer doses as compared to control. Among fertility levels, application of 50 kg N + 17.2 kg P/ha, followed by 25 kg N 8.6 kg P/ha + BF resulted in better performance of crops over other treatments.